The Comparison of Personality Characteristics and Coping Styles in Addicted and Non-Addicted Adolescents - Salman Zarei; Zahra Asadi (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: The aim of present research was to compare the personality characteristics and coping styles of addicted adolescents with normal adolescent. Method: In this ex post facto research, two groups (normal adolescent=50 and addicted adolescent=50) were selected via cluster sampling and convenience sampling respectively. Two instruments included of NEO-FFI personality questionnaire and coping style inventory were administered, then data were analyzed by using of multivariate analysis of variance. Findings: The result revealed that there was significant difference between both group in personality characteristics and coping styles. Neuroticism and emotional focused coping styles in addicted adolescent‌s were higher than normal counterparts, and on agreeableness, conscientiousness and problem solving style were lower than them. Conclusion: The finding of present study suggests that training of efficient problem solving styles to people in order to cope with life stressful events could restrain and prevent addiction and other psychosocial disorders.